DETERMINAN KEPATUHAN SELF-MANAGEMENT PADA PASIEN HIPERTENSI DI PELAYANAN KESEHATAN PRIMER - Prima Trisna Aji; Marta Tania Gabriel Ching Cing; Elinda Rizkasari (Journal Of Nursing Science Research, 2026)
Hypertension is a major global health problem with increasing prevalence and remains a leading cause of morbidity and mortality due to cardiovascular diseases. Self-management adherence plays a crucial role in blood pressure control; however, it remains suboptimal in primary healthcare settings. This study aimed to analyze the determinants of self-management adherence among hypertensive patients in primary healthcare. A quantitative study with a cross-sectional design was conducted involving 100 respondents selected through purposive sampling. Data were collected using structured questionnaires, including the Hypertension Self-Care Activity Level Effects (H-SCALE) to assess self-management adherence, as well as instruments measuring knowledge, family support, and self-efficacy. Data analysis was performed using univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses. The results showed that age (p=0.021), education level (p=0.015), duration of hypertension (p=0.032), knowledge (p=0.001), family support (p=0.002), and self-efficacy (p<0.001) were significantly associated with self-management adherence. Multivariate analysis revealed that self-efficacy was the most dominant factor influencing adherence (OR=4.67; p<0.001). In conclusion, self-management adherence among hypertensive patients is influenced by individual, social, and psychological factors, with self-efficacy as the primary determinant. Therefore, nursing interventions should focus on enhancing self-efficacy, improving health education, and involving family support to optimize hypertension management.